Design and experiment of conical diversion virus-free potato minituber precision seed-metering device - Qiu, Zhaomei; Jin, Shanshan; Jin, Xin; Ji, Jiangtao; Ma, Tengfei (International Journal of Agricultural and Biological Engineering, 2023)
In order to accelerate the development of sowing mechanization of virus-free potato minituber, a conical diversion virus-free potato minituber precision seed-metering Device was designed according to the structural characteristics and agronomic requirements of virus-free potato minituber. The device is mainly composed of conical turntable, transmission shaft, outer baffle of seed-metering Device, baffle, seed outlet, seed cleaning device, type hole, etc. The working principle of conical diversion precision seed-metering device for virus-free potato minituber was expounded, and the stress analysis of virus-free potato minituber in each region was carried out. By EDEM discrete element simulation software, the structure of the type hole is optimized to determine the optimal structure of the type hole and according to the physical characteristics of virus-free potato minituber, the single factor experiments of the effects of length of type hole, cone disc speed and cone disc angle on seed filling performance were completed. The orthogonal regression test was carried out with the length of type hole, cone disc speed, and cone disc angle as the test objects, and the leakage rate and qualified rate as the response indexes. The regression models of leakage rate, replay rate, and qualified rate were established, and the parameters of the regression model were optimized. The optimal parameter combination is that the length of type hole is 33.61 mm, the cone disc speed is 6.35 r/min, and the cone disc angle is 26.59°. Bench test was carried out under the optimal conditions, the leakage rate was 3.80%, the replay rate was 0.80%, and the qualified rate was 95.40%, which was basically consistent with the prediction results of the regression model, and met the requirements of precision sowing of virus-free potato minituber. Keywords: virus-free potato minituber, conical diversion, seed-metering device, type hole, discrete element method DOI: 10.25165/j.ijabe.20231603.7682 Citation: Qiu Z M, Jin S S, Jin X, Ji J T, Ma T F. Design and experiment of conical diversion virus-free potato minituber precision seed-metering device. Int J Agric & Biol Eng, 2023; 16(3): 85–95.